Feeling the Beat in an African Tone Language: Rhythmic Mapping Between Language and Music - Franich, Kathryn H.; Lendja Ngnemzué, Ange B. (Frontiers in Communication, 2021)
Text-setting patterns in music have served as a key data source in the development of theories of prosody and rhythm in stress-based languages, but have been explored less from a rhythmic perspective in the realm of tone languages. African tone languages have been especially under-studied in terms of rhythmic patterns in text-setting, likely in large part due to the questionable status of metrical structure and prosodic prominence asymmetries in many of these languages. Here, we explore how language is mapped to rhythmic structure in traditional folksongs sung in Medʉmba, a Grassfields Bantu language spoken in Cameroon. We show that, despite complex and varying rhythmic structures within and across songs, correspondences emerge between musical rhythm and linguistic structure at the level of stem position, tone, and syllable weight. Our results reinforce the notion that metrical prominence asymmetries are present in African tone languages, and that they play an important coordinative role in music and movement.